2022
DOI: 10.1007/s44246-022-00031-3
|View full text |Cite
|
Sign up to set email alerts
|

Air oxidation in surface engineering of biochar-based materials: a critical review

Abstract: Biochar always suffers from low porosity and/or poor surface functionality, which limit its performances. Among various surface engineering strategies, air oxidation favors both pore development and surface oxygenation for biochar. However, there is still a lack of systematic knowledge and critical perspective on air oxidation in surface engineering of biochar-based materials for various applications. Herein, this review analyzed the mechanisms of air oxidation, summarized the routes of air oxidation in surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 135 publications
1
13
0
Order By: Relevance
“…The results showed that BET specific surface area, total pore volume, micropore volume, and mesopore volume were increased from 40.93 m 2 /g for LHB to 60.42 m 2 /g for LHCB, suggesting that TAO of LHB was favorable for pore development. This observation was consistent with previous results about the TAO of various biochars. , In addition, the volumes of total pores and mesopores were more remarkably increased after TAO of LHB, suggesting that TAO was more favorable for the development of mesopores.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The results showed that BET specific surface area, total pore volume, micropore volume, and mesopore volume were increased from 40.93 m 2 /g for LHB to 60.42 m 2 /g for LHCB, suggesting that TAO of LHB was favorable for pore development. This observation was consistent with previous results about the TAO of various biochars. , In addition, the volumes of total pores and mesopores were more remarkably increased after TAO of LHB, suggesting that TAO was more favorable for the development of mesopores.…”
Section: Resultssupporting
confidence: 92%
“…During the TAO process, surface carboxyl groups will be enriched, thus La species could be complexed with these functional groups. Simultaneously, TAO also generate a large amount of CO 2 , attributed to the desorption of chemically adsorbed oxygen on biochar surface . Thus, during TAO, La species could complex with carboxyl groups and react with CO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations